Comparison of 0.1% and 0.3% Nepafenac eye drops on reduction of macular thickness and improvement of visual acuity in patients with diabetic macular edema - Dr. Rakesh Verma, Dr Rachana Gahlawat (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Macular thickening is a postoperative complication following cataractsurgery, even with uncomplicated small-incision phacoemulsification surgery.Subclinical cystoid macular edema